Performance of Multiparametric Functional Imaging to Assess Peritoneal Tumor Burden in Ovarian Cancer. (October 2021) - Mallet, Estelle; Angeles, Martina Aida; Cabarrou, Bastien; Chardin, David; Viau, Philippe; Frigenza, Mélanie; Navarro, Anne Sophie; Ducassou, Anne; Betrian, Sarah; Martínez-Gómez, Carlos; Tanguy Le Gac, Yann; Chantalat, Elodie; et al.
Abstract : Purpose: The aim of the study was to evaluate the clinical utility of pretreatment 18 F-FDG PET/CT with quantitative evaluation of peritoneal metabolic cartography in relation to staging laparoscopy for ovarian carcinomatosis. Patients and Methods: A retrospective review of prospectively collected data from 84 patients with FIGO (International Federation of Gynecology and Obstetrics) stage IIIC to IV ovarian cancer was carried out. All patients had a double-blinded 18 F-FDG PET/CT review. Discriminant capacity of metabolic parameters to identify peritoneal carcinomatosis in the 13 abdominal regions according to the peritoneal cancer index was estimated with area under the receiver operating characteristic curve (AUC). Results: The metabolic parameter showing the best trade-off between sensitivity and specificity to predict peritoneal extension compared with peritoneal cancer index score was the metabolic tumor volume (MTV), with a Spearman ρ equal to 0.380 ( P < 0.001). The AUC of MTV to diagnose peritoneal involvement in the upper abdomen (regions 1, 2, and 3) ranged from 0.740 to 0.765. MTV AUC values were lower in the small bowel regions (9–12), ranging from 0.591 to 0.681, and decreased to 0.487 in the pelvic region 6. 18 F-FDG PET/CT also improved the detection of extra-abdominal disease, upstaging 35 patients (41.6%) from stage IIIC to IV compared with CT alone and leading to treatment modification in more than one third of patients. Conclusions: 18 F-FDG PET/CT metrics are highly accurate to reflect peritoneal tumor burden, with variable diagnostic value depending on the anatomic region. MTV is the most representative metabolic parameter to assess peritoneal tumor extension. Abstract : Supplemental digital content is available in the text.